THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES ABOUT THE VARIOUS SNACK CHOICE WITH THE FOOD SELECTING OF CHILDREN’S BEHAVIOR IN SDN SAMBIKEREP II/480 SURABAYA - SUDARMAWAN, (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Snack choice is one of the types of foods that are very well known and common in the community, especially school-age children. Snack choice that contains nutrients, securely packaged and processed has a special attraction for the community. School children usually buy food at the hawker street food vendors hawked around the school or in the school cafeteria. Therefore, traders play an important role in the provision of healthy food and nutritious snacks as well as safety. With so many foods that contain harmful chemicals on the market, school canteens and food vendors around the school is that the seller can make students eat unhealthy foods. The purpose of this study to deter`mine the relationship between knowledge and attitudes regarding the selection of snack choice to choose foods with the child's behavior in public elementary schools Sambikerep II/480 Surabaya. Objective of this study is class VA and VB Sambikerep II/480 primary schools who are 71 students Surabaya. This research is a descriptive study. Data retrieval by filling out questionnaires. The results of this research are: 1) That there is a relationship between knowledge and attitudes regarding the selection of snack foods with the child's behavior in choosing food SDN II/480 Sambikerep Surabaya, for testing the significance of the multiple correlation coefficients are yielding significant probability of 0,027 < significance level of 0,05, tested the correlation coefficient is significant. 2) There is a relationship between knowledge and attitudes of young children with behavior in choosing food SDN II/480 Sambikerep Surabaya with a contribution of 10.1%. Keywords: Knowledge, Attitude, Behaviour, Selecting Food.